The effects of progressive-resisted exercises on muscle strength and health-related quality of life in persons with HIV-related poly-neuropathy in Zimbabwe. Issue 5 (3rd May 2016) - Mkandla, Khumbula; Myezwa, Hellen; Musenge, Eustasius
ABSTRACT: Distal symmetrical poly-neuropathy (DSP) is a neurological complication associated with HIV/AIDS and stavudine (d4T) containing antiretroviral therapy. People with DSP experience pain, numbness and muscle weakness, which affect their quality of life (QOL). The purpose of this study was to establish the effect of a progressive-resisted exercise (PRE) intervention on health-related quality of life (HR-QOL) in people living with HIV/AIDS-related DSP. An assessor-blinded randomised controlled trial was conducted, with participants sourced from 10 clinics with HIV services, the family care clinic at Wilkins Hospital and 2 large hospitals in Harare, Zimbabwe. A 12-week PRE intervention was conducted twice weekly for 80 participants, while the control group with 80 participants continued with usual daily activities. The main outcome variable was HR-QOL for which we controlled for demographic and clinical measures in generalised estimating equation population-averaged models. Data were summarised and analysed using an intention to treat analysis approach using the Stata v10 program. Mean age of participants was 42.2 years (SD = 8.5). While d4T was used by 59% ( n = 94), an equal proportion of the participants also had moderate to severe neuropathy. PRE was found to significantly improve HR-QOL in the intervention group based on the mean difference between the intervention group mean change and the mean change in the control group ( F ratio 4.24; p = .04). This study established that PREs have positive effects on HR-QOL for people living with HIV/AIDS-related DSP.